Literature Review: Analysis of K3 Implementation in Textile Industry Companies - Nurhasanah, Siti Aldina (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
Occupational Safety and Health (K3) has a crucial role in projects with a high risk of work accidents. Non-compliance with the implementation of the Occupational Health and Safety Management System (SMK3) can have serious impacts on humanitarian, economic, environmental, and legal aspects. The close relationship between workers and work accidents has an impact on productivity, making the application of SMK3 an important factor in human resource development. SMK3 not only protects workers in the company, but also involves protecting the community from the dangers caused by industrial products. The risk of hazards in the work environment can hamper worker safety and health conditions, reduce efficiency, and interfere with organizational effectiveness. Law Number 1 of 1970 regulates the implementation of K3 in all workplaces in Indonesia, including land, in the ground, on the surface of the water, in the water, and in the air. SMK3 is the most important part in the risk management of a company or organization. In an effort to form an effective SMK3, companies need to internalize awareness of the importance of K3 and provide education to employees about safety and health in the workplace. Work accident cases can cause worker suffering, decreased production, and financial losses for the company. This study conducted a literature review on the application of K3 in the textile industry. This research method is literature review with a qualitative approach. Data obtained from scientific articles/journals using Google Scholar with the keyword